Impact of different alcohol beverages on cardiovascular system - Piotr Wójcik; Maciej Sobczyk; Małgorzata Słaboń; Małgorzata Chyćko; Piotr Więsyk; Monika Rogowska; Jan Tomczyk; Paulina Oleksa; Mateusz Sobczyk (Kazimierz Wielki University, 2021)
Introduction: Alcohol is one of the most widely-used stimulants. It's easily accessible, most socially accepted and usually not associated with potential harm it can do. Except for its addictive effect, it has a strong influence on humane systems.   In this analysis the influence of alcohol on the cardiovascular system will be examined. As it is not obvious whether alcohol usage should be only associated with harmful impact on cardiac activity, different types of alcoholic beverages should be examined.   In this work three different sub-groups will be analyzed. They were selected and divided by the beverage type and percentage as follows: beer, wine, high percentage liquors. As the majority of studies show, it's important to underline the significance of not only the alcohol percentage implied, but mostly of the alcohol type. In favor of alcoholic beverages are only studies analyzing beverages containing low levels of alcohol, but abundant in other organic substances like resveratrol (in wine). Other studies considering other beverages, nonetheless of alcohol levels, diminishing effect on the cardiovascular (and other) systems is observed.    Material and methods: An analysis of scientific papers from Pubmed Google Scholar was performed, wchoch most accurately described the issue of diffrent type of alcohol bevereage on human health. The following keywords were used in search: alcohol, cardiovascular, wine, beer, spirits.  Purpose of the work: Aim of the following analysis is to systematize the knowledge based on latest research and findings about the impact of different alcohol beverages on cardiovascular system.